Likelihood-based inference in cointegrated vector autoregressive models - Johansen, S. (Oxford University Press, 2012)
Throughout the period of preparing this monograph I have had the pleasure of collaborating with Katarina Juselius, who introduced me to the topic of cointegration by asking me to give some lectures on the basic paper by Clive Granger (1983). Since then we have worked on developing the theory in close contact with the applications, and the results we have obtained have been driven by the need to understand the variation of economic data. Thus the theory has been forced upon us by the applications, and the theory has suggested new questions that could be asked in practice. I feel fortunate in having had the opportunity for this type of collaboration, and would like to use this opportunity to thank Katarina for being so inspiring.